Comparative sequence analysis of the P-, M- and L-coding region of the measles virus CAM-70 live attenuated vaccine strain - Santos,P.R. (2003)
Measles virus is a highly contagious agent which causes a major health problem in developing countries. The viral genomic RNA is single-stranded, nonsegmented and of negative polarity. Many live attenuated vaccines for measles virus have been developed using either the prototype Edmonston strain or other locally isolated measles strains. Despite the diverse geographic origins of the vaccine viruses and the different attenuation methods used, there was remarkable sequence similarity of H, F and N genes among all vaccine strains. CAM-70 is a Japanese measles attenuated vaccine strain widely used in Brazilian children and produced by Bio-Manguinhos since 1982. Previous studies have characterized this vaccine biologically and genomically. Nevertheless, only the F, H and N genes have been sequenced. In the present study we have sequenced the remaining P, M and L genes (approximately 1.6, 1.4 and 6.5 kb, respectively) to complete the genomic characterization of CAM-70 and to assess the extent of genetic relationship between CAM-70 and other current vaccines. These genes were amplified using long-range or standard RT-PCR techniques, and the cDNA was cloned and automatically sequenced using the dideoxy chain-termination method. The sequence analysis comparing previously sequenced genotype A strains with the CAM-70 Bio-Manguinhos strain showed a low divergence among them. However, the CAM-70 strains (CAM-70 Bio-Manguinhos and a recently sequenced CAM-70 submaster seed strain) were assigned to a specific group by phylogenetic analysis using the neighbor-joining method. Information about our product at the genomic level is important for monitoring vaccination campaigns and for future studies of measles virus attenuation.